Wakaf Pertanian Sebagai Instrumen Pemberdayaan Ekonomi Masyarakat Pedesaan (Studi Survei: Yayasan Perluasan dan Pengembangan Wakaf Pondok Modern Gontor) - bin Lahuri, Setiawan; Chania Mutia Wardani; Ainun Amalia Zuhroh (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2025)
This study aims to identify the management of agricultural waqf in YPPWPM Gontor Mantingan branch towards community economic empowerment. This study used a measuring instrument called NTP (Farmer Exchange Rate), by looking at income, education, health and settlements in the area where the farmers live. The method used is a qualitative approach. The data obtained using the triangulation method with the results of interviews, observations and documentation. From a random population of 114 farmers who work on land owned by the foundation, this study used 10 respondent samples. The results of the study are presented in descriptive form. The results of the study show that farmers who manage YPPWPM waqf land can be said to be empowered, because these farmers are given capital in the form of waqf land to be planted with rice, which then the harvest of the rice will be divided between the Foundation and the farmers, or commonly called profit sharing. All forms of capital in cultivation are borne by the cultivators starting from seeding, plowing using tractors, administering drugs, all borne by the farmers. This is usually divided by the Foundation into three parts, namely 1/3 for the net profit received by the farmers, 1/3 for the Foundation, and 2/3 for the cultivation capital.